Subjective hunger sensations and prospective food intake in obese and overweight subjects: influence of ethnicity - Muhardi, Leilani Lestarina (Curtin University, 2015)
The thesis assessed the potential impact of ethnicity on subjective sensations of hunger and food intake. In a cross-sectional design, 18 Asians and 26 Europid overweight/ obese Australians had hunger/satiety sensations tracked before and for 2h after an oral glucose load. Prospective food intake was recorded at a buffet meal and over 24h. There were no differences in hunger/satiety sensations and food intake between ethnic groups but history of weight stability interacted with ethnicity to influence outcomes.